KARAKTERISTIK BAHASA LISAN SISWA KELAS 1 SDN PENDEM I MAGETAN DALAM INTERAKSI BELAJAR MENGAJAR TAHUN AJARAN 2013/2014 - Puspitasari, Dhika; Furinawati, Yunita; Pratama, Dihtia Rendra (IKIP PGRI MADIUN, 2015)
The purpose of this research is : ( 1 ) describe the form of spoken language first grade students of SDN Pendem I Magetan in teaching and learning interactions , and ( 2 ) describe the characteristics of spoken language first grade students of SDN Pendem I Magetan . The object of this research is the spoken language students in first grade SDN Pendem I Magetan when interacting with the teacher in teaching and learning activities. Outcomes of this study that this research will be uploaded in national journals accredited Lentera ( State University of Yogyakarta ) , Journal Pendidikan IKIP PGRI Madiun , and Journal Widyabastra. This study refers to the spoken form of the language description which includes the word class , the form of words , and sentence structure. Word class consists of verbs , nouns, adjectives , adverbs , and word tasks. While the form of a word composed of affix words , repeated words , compound words , and acronym. Sentence structure includes six basic sentence patterns . This study used a qualitative descriptive method . Descriptive methods showed that the study presented here is done solely based on the fact that there is or phenomena that are empirically living in speakers . Collecting data in this study using the methods refer to the tapping technique .Keywords: characteristics, spoken language, word class, word form, sentence structure